След "оборотня": роман / Н. И. Леонов - Леонов Н. И. (Лучшие романы Н. Леонова, 2013)
Экземпляры: аб. ЦБ (20200323) / Инвентарный номер: 8984 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л 47 / ББК: 84(2Рос=Рус)6